AL-AMR DALAM AL-QUR’AN SURAH AṢ-ṢᾹFFᾹT (DIRĀSAH TAḤLῙLIYAH FῙ ‘ILM AL- MAʻĀNῙ) - Basri, Kurnia; Muhammad, Aksa (Al-Syamail: Jurnal Bahasa dan Sastra Arab, 2024)
Al-Amr in the Qur’an Surah aṣ-Ṣāffāt (An Analytical Study in the Science of Meanings) (Supervised by H. Muh. Iqbal Hasanuddin and Aksa Muhammad Nawawi). In the context of the Qur’an, al-amr refers to the form of a verb or phrase that indicates a command or instruction given by Allah to His servants. This command can be an obligation, prohibition, or recommendation that Muslims must follow. This study discusses al-amr in the Qur’an, specifically in surah aṣ-Ṣāffāt, by examining two main issues: the forms of al-amr and the meanings of al-amr in surah aṣ-Ṣāffāt. The aim is to identify the forms of al-amr and understand their meanings in surah aṣ-Ṣāffāt. The research method used is a library study, encompassing the search, classification, and analysis of data sources such as the Qur’an, books, and theses related to al-amr in surah aṣ-Ṣāffāt, which are then analyzed using the science of meanings (ʻIlm al-Maʻānῑ). The research results show that in surah aṣ-Ṣāffāt there are two ṣigah or forms of al-amr, namely fi‘il amr (imperative verb) and fi‘il mudāri (present tense verb) that begins with lam amr (lam of command). Seventeen words in the form of fi‘il amr and one word in the form of fi‘il mudāri were found. The meanings of al-amr found in this surah are divided into two main categories: The literal meaning found in verses 11, 18, 22, 23, 24, 73, 149, 157, 174, 175, 178, and 179, indicating a direct command without additional interpretation. The rhetorical meaning is divided into three: the meaning of guidance (irsyad) in verses 61 and 102, the meaning of request (iltimas) in verse 97, and the meaning of supplication (do‘a) in verse 100.